2019
DOI: 10.1109/access.2019.2909573
|View full text |Cite
|
Sign up to set email alerts
|

The Study of a Classification Technique for Numeric Gaze-Writing Entry in Hands-Free Interface

Abstract: Recently, many applications are developed in numerous domains with various environments. Since some environments require hands-free applications, new technology is needed for the input interfaces other than the mouse and keyboard. Therefore, to meet the needs, many researchers have begun to investigate the gaze and voice for the input technology. In particular, there are many approaches to render virtual keyboards with the gaze. However, since the virtual keyboards hide the screen space, this technique can onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Based on Table 1, most of the studies showed a positive result from the performance. The highest accuracy obtained was 99.3 (Lagodzinski et al, 2018) and 99.21% (Yoo et al, 2019), with the features of EOG and gaze position, respectively. The study of Guo et al (2021) has the lowest accuracy among the studies found, which achieved an accuracy of 49.32%.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Based on Table 1, most of the studies showed a positive result from the performance. The highest accuracy obtained was 99.3 (Lagodzinski et al, 2018) and 99.21% (Yoo et al, 2019), with the features of EOG and gaze position, respectively. The study of Guo et al (2021) has the lowest accuracy among the studies found, which achieved an accuracy of 49.32%.…”
Section: Discussionmentioning
confidence: 94%
“…In a study by Kacur et al (2019), the authors presented a method for the detection of schizophrenia disorders using gaze position with the Rorschach Inkblot Test. In a study by Yoo et al (2019), a gazewriting classification technique for numeric gaze-written entry is proposed.…”
Section: Pupil Positionmentioning
confidence: 99%
“…Another group of research has focused on developing prediction models. Studies have employed machine learning algorithms (e.g., Support Vector Machine (SVM), Logistic Regression, Random Forest, k -Nearest Neighbors, Na ve Bayes), and more recent studies have begun to utilize deep learning methods (Convolutional Neural Network (CNN) and Long Short-Term Memory (LSTM)) to extract deep features of the data and construct a more complicated learning models [ 18 , 21 , 22 ]. These studies have utilized various types of features extracted from sensor signals as the data for their prediction models and demonstrated high possibilities of predicting users’ states or behaviors through their models.…”
Section: Introductionmentioning
confidence: 99%